SYMPOSIUMS “CHALLENGENG ROAD TO LONG-TERM CONTROL OF BRONCHIAL ASTHMA: HOW TO BUILD A ROUTE?” AND “EARLY INTERVENTION IN THE MANAGEMENT OF PATIENTS WITH ATOPIC DERMATITIS” - article Editorial (Педиатрическая фармакология)
.